Audiological profile of patients treated for childhood cancer, - Liberman,Patricia Helena Pecora (2016)
Abstract Objective: To characterize the hearing loss after cancer treatment, according to the type of treatment, with identification of predictive factors. Methods: Two hundred patients who had cancer in childhood were prospectively evaluated. The mean age at diagnosis was 6 years, and at the audiometric assessment, 21 years. The treatment of the participants included chemotherapy without using platinum derivatives or head and neck radiotherapy in 51 patients; chemotherapy using cisplatin without radiotherapy in 64 patients; head and neck radiotherapy without cisplatin in 75 patients; and a combined treatment of head and neck radiotherapy and chemotherapy with cisplatin in ten patients. Patients underwent audiological assessment, including pure tone audiometry, speech audiometry, and immittancemetry. Results: The treatment involving chemotherapy with cisplatin caused 41.9% and 47.3% hearing loss in the right and left ear, respectively, with a 11.7-fold higher risk of hearing loss in the right ear and 17.6-fold higher in the left ear versus patients not treated with cisplatin (p < 0.001 and p < 0.001, respectively). Children whose cancer diagnosis occurred after the age of 6 have shown an increased risk of hearing loss vs. children whose diagnosis occurred under 6 years of age (p = 0.02). Conclusion: The auditory feature found after the cancer treatment was a symmetrical bilateral sensorineural hearing loss. Chemotherapy with cisplatin proved to be a risk factor, while head and neck radiotherapy was not critical for the occurrence of hearing loss.